c-Fos-activated synthesis of nuclear phosphatidylinositol 4,5-bisphosphate[PtdIns(4,5)P2] promotes global transcriptional changes - Ferrero, Gabriel Orlando (2014)
c-Fos is a well-recognized member of the AP-1 (activator protein-1) family of transcription factors. In addition to this canonical activity, we previously showed that cytoplasmic c-Fos activates phospholipid synthesis through a mechanism independent of its genomic AP-1 activity. c-Fos associates with particular enzymes of the lipid synthesis pathway at the endoplasmic reticulum and increases the Vmax of the reactions without modifying the Km values. This lipid synthesis activation is associated with events of differentiation and proliferation that require high rates of membrane biogenesis. Since lipid synthesis also occurs in the nucleus, and different phospholipids have been assigned transcription regulatory functions, in the present study we examine if c-Fos also acts as a regulator of phospholipid synthesis in the nucleus. Furthermore, we examine if c-Fos modulates transcription through its phospholipid synthesis activator capacity. We show that nuclear-localized c-Fos associates with and activates PI4P5K (phosphatidylinositol-4-monophosphate 5-kinase), but not with PI4KIIIβ (type IIIβ phosphatidylinositol 4-kinase) thus promoting PtdIns(4,5)P2 (phosphatidylinositol 4,5-bisphosphate) formation, which, in turn, promotes transcriptional changes. We propose c-Fos as a key regulator of nuclear PtdIns(4,5)P2 synthesis in response to growth signals that results in c-Fos-dependent transcriptional changes promoted by the newly synthesized lipids.